Anthropomorphic Design in Mortality Salience Situations: Exploring Emotional and Non-Emotional Mechanisms Enhancing Consumer Purchase Intentions - Cong Sun; Yuechun Ding; Xinyi Wang; Xing Meng (Behavioral Sciences)
This study investigates the role of anthropomorphic design in alleviating consumer anxiety induced by mortality salience and delves into the underlying emotional and non-emotional mechanisms. Through a series of meticulously designed experiments, we confirm that anthropomorphic design significantly enhances positive emotional responses in consumers, reduces negative emotions, and thereby increases their preference and willingness to purchase products. Even after the diminution of emotional reactions, anthropomorphic design continues to sustain consumer preference by enhancing psychological intimacy. These findings reveal the crucial role of anthropomorphic design as an effective emotional regulation strategy in consumer purchasing behavior, enriching the application of terror management theory and emotion regulation theory in consumer behavior research. Furthermore, our study provides valuable practical guidance for product design and marketing strategies, especially for consumer groups frequently facing high-pressure situations. Products with anthropomorphic designs may be more appealing to these consumers, helping to mitigate their death anxiety and enhance psychological well-being.